El ruido ambiental y la salud en el poblador del Centro Histórico de Cajamarca, Perú 2017 – 2018 - Grau Chavez, Walter Aldo (2019)
ABSTRACT We investigated the noise pollution and its effects on anxiety in residents of the city of Cajamarca, Peru. First, sound pollution was determined in 162 urban Cajamarca blocks, using the Standard proposed by Querol (1994), and anxiety levels through the Zung Anxiety Test, identifying a critical noise pollution situation of 65.7-100 , 9 dB A. The regression coefficient was used to process the results, which indicate a relationship of increasing dependence between the noise and anxiety variables, with predominance in the elderly. It was concluded that if there is a linear and positive relationship between levels of noise pollution and those of anxiety, with a value of 0.9411 to 0.9932.